Nxopaxopo wa mathyelo ya tindhawu emigangeni ya le Mhala Exifundzeni xa Bohlabela : Maendlelo ya matumbulukelo - Mhlongo, Thomas Mavele (University of Limpopo, 2013)
The study examines the origin of place names and naming patterns of some communities in Mhala Sub-district in Bohlabela district in Mpumalanga Province. The study will deal with the various reasons underlying the naming of these place names and their origins. Furthermore the study will seek to find out how these place names were of great significance in that they are meaningful and preserve history. In order to achieve the aims of the proposal, the researcher will employ the qualitative research method. This qualitative research method will be supported by both primary and secondary methods in terms of data collection. The study will make people aware of the reflection of the value, importance and meaning attached to place names since it shows how people name their different places, which are in most instances body of history and meaningful. In other words, the study will endeavour to contribute to existing body of knowledge and understanding of the naming practices of some place names in Mhala sub-district of Bohlabela district in Mpumalanga Province.
Thesis (M. A. (African Languages)) -- University of Limpopo, 2013
Keywords: Place names; Communities; Mhala District; Greater Bohlabela District; Tsonga language; Names, Geographical - Etymology.